2012
DOI: 10.1002/gps.2821
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depressive symptoms among the older in China: a meta‐analysis

Abstract: The prevalence of depressive symptoms among the older in China was a little high, and it was varied by gender, age, area, and education level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 36 publications
7
78
3
2
Order By: Relevance
“…The results revealed a prevalence rate of 11.6% among CDEP, which was similar to the findings of many previous studies in China (Chen et al, 2005;Phillips et al, 2009;Zhang et al, 2012;Li et al, 2012). The prevalence rate of hospitalized elderly people was relatively higher (18.1%), but it was slightly lower than the rates found in previous studies based on hospitalized population in China (Zhang et al, 2008;Liu et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results revealed a prevalence rate of 11.6% among CDEP, which was similar to the findings of many previous studies in China (Chen et al, 2005;Phillips et al, 2009;Zhang et al, 2012;Li et al, 2012). The prevalence rate of hospitalized elderly people was relatively higher (18.1%), but it was slightly lower than the rates found in previous studies based on hospitalized population in China (Zhang et al, 2008;Liu et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Studies on Chinese elderly people indicated that the prevalence rate of geriatric depression ranged from 6% to 27% (Chen et al, 2005;Phillips et al, 2009;Zhang et al, 2012;Li et al, 2012). However, most of the existing studies were based on community population, and little was known about geriatric depression among institutionalized population.…”
mentioning
confidence: 95%
“…Although there are some controversies related to the relevant study’s design, it has been shown that females express more hypochondriac concerns than males [29]. Moreover, because depression has been reported to be more prevalent in women, we presume that women are more likely than men to demonstrate overestimation of hearing loss [30]. However, female sex was not related to overestimation of hearing loss in this study (AOR = 0.86, [95% CI = 0.73–1.01]).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis shows that the mean pooled prevalence rate of depression in rural older Chinese was 29.2%, significantly higher than it was in urban older Chinese (20.5%) (Zhang, Xu, Nie, Zhang, & Wu, 2012). Most prior studies have not controlled for other factors when examining the association between rural-urban strata and late-life depression.…”
mentioning
confidence: 99%